Anthropometric measures associated with diabetes mellitus: a comparative cross-sectional study among adults availing health services in an urban underprivileged area of Bangalore city - Mundra, Mahin; Masih, Sanglap; Thomas, Johann; Johnson, Avita Rose (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetes affects about 12% of urban Indian adults. Obesity is a key risk factor, measurable through several anthropometric indices. This study examined which measures are most strongly associated with diabetes among adults in an underprivileged urban area of Bangalore. Methods: A comparative cross-sectional study was conducted among adults aged ≥30 years attending a health centre. Socio-demographic, lifestyle, and dietary data were collected. Anthropometric parameters including body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), and waist-to-calf ratio (WCR) were assessed and compared between 84 diabetics and 84 non-diabetics. Independent t-test and Mann Whitney U tests were performed. Results: Diabetics were over six times more likely to have higher WCR than non-diabetics (AOR=6.43; 95% CI: 1.90-21.7; p=0.003). No significant differences were found for BMI, WC, WHR, or WHtR. Dietary patterns differed significantly: diabetics were more likely to lack daily fruit and vegetable intake (AOR=3.2; 95% CI: 1.27-8.12; p=0.002) and more likely to consume fried, salty, or junk foods daily (AOR=9.14; 95% CI: 4.09-20.41; p<0.001). No notable differences were observed in hypertension, alcohol use, smoking, or physical activity. Conclusions: Waist-to-calf ratio (WCR) is a significant marker of diabetes in this urban Indian population, alongside unhealthy dietary habits. Establishing appropriate WCR cut-offs could help identify high-risk individuals and guide early preventive interventions.